On Ga2O3 Self‐Switching Nano‐Diodes - Glen Isaac Maciel García; Jorge Esteban Bolio; Vishal Khandelwal; Ganesh Mainali; Jose Taboada; Haicheng Cao; Biplab Sarkar; Xiaohang Li (Advanced Electronic Materials, 2025)
Abstract In this work, a Ga₂O₃ self‐switching nano‐diode (SSND) fabricated on a sapphire substrate is presented. Unlike previous SSND studies that primarily focused on rectification, this work explores additional device characteristics, including breakdown voltage and photodetection functionality. The diode exhibits increased current with the increase in the relative permittivity (κ) of the device trenches, and under UV illumination. Devices with increased κ achieve a high current density of ≈10 kA cm−2, a rectification ratio of ≈10⁴, and a specific on‐resistance as low as 0.29 mΩ cm2. They also exhibit a breakdown voltage greater than 100 V, and a maximum power figure‐of‐merit of 35.46 MW cm−2. Moreover, under 240 nm light illumination, the diodes showed a responsivity close to 104 A W−1. These initial results demonstrate the potential of the SSNDs toward monolithic Ga₂O₃ circuits that are currently under extensive investigation for various applications.